If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + x + -1 = -1 + 2x Reorder the terms: 8 + -1 + x = -1 + 2x Combine like terms: 8 + -1 = 7 7 + x = -1 + 2x Solving 7 + x = -1 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 7 + x + -2x = -1 + 2x + -2x Combine like terms: x + -2x = -1x 7 + -1x = -1 + 2x + -2x Combine like terms: 2x + -2x = 0 7 + -1x = -1 + 0 7 + -1x = -1 Add '-7' to each side of the equation. 7 + -7 + -1x = -1 + -7 Combine like terms: 7 + -7 = 0 0 + -1x = -1 + -7 -1x = -1 + -7 Combine like terms: -1 + -7 = -8 -1x = -8 Divide each side by '-1'. x = 8 Simplifying x = 8
| 2+3lnx=7 | | -41x=451 | | 5-2+9=-16 | | 25-9x=1-x | | 4m-((2m+n)-(4m-7n)+(2m-8n))= | | 7-(-1-6x)=4x-8 | | -5-8=-5h+8 | | -(3x+2)=4 | | 6x-(4x+8)=4x-14 | | -108/9=9/9j | | 2=8+3y | | 3x+12=2(x-(4-x)) | | 3(s-4)+s=-5s+51 | | 3-1/5x-4 | | 4.4x=-0.8x | | 5x-2-7x=4 | | 5x+6=10x+1 | | 6(x-3)=10x | | 5-x-2=4x+3+4x+5 | | 12q=155 | | y^2-xy+3=-xy+y+y^2 | | 1=3x+11 | | -1/6y=7 | | 4x+4=5(x-4) | | 25=2y-5 | | -12=2(2-x) | | U^4-u^2+36=0 | | -8(3v-5)=23-7v | | -21=n-1 | | b+-2=0 | | 2/3x12= | | 11x=4-2 |